Silicon-Induced General, Mild, and Efficient One-Pot, Three-Component Synthesis of Amidoalkyl Naphthol Libraries - Salama, Tarek A. (Synlett, 2013)
A general mild and efficient protocol for the synthesis of amidoalkyl naphthol libraries was achieved utilizing tetrachlorosilane and zinc chloride in dichloromethane at ambient temperature via a one-pot, three-component condensation of various aldehydes, nitriles (amides), and β-naphthol.
Keywords: multicomponent reactions; amidoalkyl naphthols; tetrachlorosilane; Ritter reaction; combinatorial synthesis